2016
DOI: 10.17265/1548-6648/2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Diabetic Retinopathy among Diabetes Mellitus Patients Attending the Colombo South Teaching Hospital, Sri Lanka

Abstract: INTRODUCTION: Diabetic retinopathy is a chronic, progressive and potentially sight threatening disease and the most commonly diagnosed complication of diabetes. Its incidence increases with prolonged duration of diabetes and accounts for a significant amount of morbidities that are directly related to diabetes as it is one of the leading causes of visual handicap. This study was conducted to assess the knowledge of diabetic retinopathy among diagnosed diabetic patients, attending clinics at the Colombo South T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Study conducted at other places also revealed significant relation between duration and knowledge. [14,15,16] In the present study, about 70% gave correct response to the questions to assess the knowledge and about 25% were not aware of the disease. Studies conducted at Colombo showed only 31% having good knowledge.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Study conducted at other places also revealed significant relation between duration and knowledge. [14,15,16] In the present study, about 70% gave correct response to the questions to assess the knowledge and about 25% were not aware of the disease. Studies conducted at Colombo showed only 31% having good knowledge.…”
Section: Discussionmentioning
confidence: 48%
“…Studies conducted at Colombo showed only 31% having good knowledge. [14] Ramiz Hussain et al reported 619 (40.7%) out of 1538 patients with diabetes mellitus to have good knowledge of the disease [ 15,16 ]. In our study, 32.4% were unaware that DR depends on duration of the disease and 24% did not know that DR leads to blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Geethadevi M et al 30 found that 60.8% had no knowledge of diabetic retinopathy and Panigrahi S et al 31 reported that 69.0% of the study population had poor knowledge of diabetic retinopathy. This implies that a significant proportion of diabetic patients have poor knowledge of diabetic DR and that there is a need for educational program about DR. 32 Concerning the relation between participants' knowledge in pre/post tests and socio-demographic characteristics, these results revealed the lowest mean knowledge score 5.20±0.1 was seen in illiterate respondents while in educated respondents it was 5.74±0.2 and became 16.56 ±1.8 and 16.69±1.8 respectively in post-test, with a statistically significant relation of p-value <0.001. This further supports the proposition that education is important in creating awareness and education has a significant role in improving patients' information.…”
Section: Discussionmentioning
confidence: 88%
“…Also, literates had more knowledge with 28% as compared to 6.7% for the illiterates. Bimalka Seneviratne 19 in Sri Lanka found that 49.5% literate patients had good knowledge about DR, while only 12.5% illiterate patients.…”
Section: Gendermentioning
confidence: 98%
“…This may be due to the increased number of visits to the physician and hence greater chances of being better aware of diabetic eye disease. In a study conducted by Bimalka Seneviratne 19 in Sri Lanka, they found that 76.3% patients having diabetes for less than 5 years had poor knowledge regarding DR, while 58.5% patients having diabetes for more than 5 years had good knowledge.…”
Section: Gendermentioning
confidence: 99%